Analysis of SRPMK Implementation in PLN Office Building Design in Kupang City - Frianggi Sofia Doresta Mansari; Dion Valerio Lilu; Reyneldis L Fernandez (Journal of Creative Power and Ambition (JCPA), 2026)
Kupang City is located in a region with high seismic risk; Therefore, building design must comply with earthquake-resistant structural standards. This study aims to analyze the implementation of the Special Moment Resisting Frame System (SMRFS) in the structural planning of the PLN Office Building in Kupang City based onSNI 1726: 2019AndSNI 2847 : 2019.The research focuses on evaluating structural performance in terms of interstory drift, structural element capacity, application of the strong column–weak beam concept, and reinforcement detailing for seismic resistance. The study employed an engineering analysis approach using three-dimensional structural modeling with ETABS V20 software. The building analyzed is a three-story reinforced concrete office structure subjected to dead loads, live loads, and earthquake loads through equivalent static and response spectrum analyses. The results indicate that the maximum interstory drift reached 21,208 mm in the Y direction on the third floor, which is still below the allowable limit of 62 mm specified inSNI 1726: 2019. The designed structural dimensions consist of 40 × 60 cm main beams, 30 × 40 cm secondary beams, 60 × 60 cm columns, and 150 mm floor slabs. Shear capacity verification showed that the nominal shear strength exceeded the factored shear force, indicating adequate safety against shear failure. Furthermore, the strong column–weak beam requirement was satisfied because the column moment capacity was greater than that of the beams. Therefore, the implementation of SMRFS provides adequate strength, stiffness, stability, and ductility for resisting design earthquake loads.